1996
DOI: 10.1159/000310705
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Uveitis Associated with Chronic Active Epstein-Barr Virus Infection

Abstract: Ocular complications of chronic active Epstein-Barr virus infection (CAEBV) have rarely been reported. We describe a 7-year-old girl with CAEBV with associated uveitis. The patient was first observed to have recurrent fever and hepatos-plenomegaly in August 1991. She presented with left facial nerve palsy in June 1993. Ocular examination showed right iridocyclitis. Both optic disks were swollen, and the retinal vessels were dilated. Antibody titers to EBV were markedly elevated. Treatment with topical steroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…Our cases were different from those reported by Wong et al [2]and Morishima et al [3]. The unilateral optic disk was swollen and fluorescein angiography showed hyperfluorescence of the optic disk.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our cases were different from those reported by Wong et al [2]and Morishima et al [3]. The unilateral optic disk was swollen and fluorescein angiography showed hyperfluorescence of the optic disk.…”
Section: Discussioncontrasting
confidence: 99%
“…Bilateral uveitis was noted in all patients, ranging from an anterior uveitis to severe panuveitis. Morishima et al [3]also reported a case of uveitis with CAEBV. A 7-year-old girl showed right iridocyclitis, a swelling of both optic disks and dilatation of retinal vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been reported in various ocular lesions,2,5 it is usually limited to a transient follicular conjunctivitis. Only two cases of unilateral optic swelling due to CAEBV have been reported, and in both cases, CAEBV with recurrent fever had been diagnosed before the onset of ocular symptoms 4.…”
Section: Commentsmentioning
confidence: 99%